Exporting and the wage premium: The case of South African manufacturing firms. Issue 4 (22nd July 2021) - Bezuidenhout, Carli; Matthee, Marianne; Rankin, Neil
Abstract: There is much literature to support the view that exporters (both developed and developing countries) pay higher wages than nonexporters. While this so‐called export wage premium has also been found to be prevalent in South Africa, it has not been thoroughly researched, with studies to date having relied on cross‐sectional sample data rather than on the population of firms and workers. Using a newly constructed employer–employee matched panel data set on South African manufacturing firms, the study examined the factors contributing to the export wage premium in these firms—from firm, individual, and job characteristics (both observable and unobservable) to firms' distribution of wages and export destinations (e.g., SACU‐only [Firms exporting only to Southern African Customs Union countries], Africa‐only [Firms exporting only to African countries], or international [Firms exporting to both African and non‐African countries]). One of the key findings was that the export wage premium is not about being labeled an exporter. It is, however, because of the "type of firm" (unobservable firm characteristics) exporters are, the "type of workers" (unobservable individual characteristics) they employ, and the "type of jobs" (unobservable job characteristics) they create. Policymakers should therefore be aware that simply expanding the pool of exporters will not necessarily give momentum to the export wage premium phenomenon. Rather, policy measures should be aimed at increasing firm‐level productivity.